Hubungan Pengetahuan dan Praktik Pemberantasan Sarang Nyamuk (PSN) Dengan Bionomik Vektor Demam Berdarah Dengue (DBD) di Kelurahan Ngaliyan Kota Semarang - Dewi, Risma Shinta; Sutiningsih, Dwi; Martini, Martini (Jurnal Riset Kesehatan Masyarakat, 2024)
Dengue Hemorrhagic Fever (DHF) is still becoming health problem  appeared in Semarang. Ngaliyan district is endemic area of DHF. People's behavior plays a role in the availability of container and the existence of larvae. The purpose of this research is to analize the relation between the knowledge and PSN practice with dengue vector bionomic in Ngaliyan. This research used cross sectional design. Sample was taken using purposive sampling technic based on the highest DHF case. The research sample 300 houses in total includes 100 houses in RW II, 100 houses in RW V, 100 houses in RW VI. The measuring of knowledge variable  and PSN practice used quissioner meanwhile vector bionomic variable used observation paper. Statistic analyse was done using chi square test. The result showed that Ngaliyan district was the area which has high possibility of DHF transmission with HI 30%, Cl 10,7% and BI 39,67. The identification of 593 mosquito in Ngaliyan district, 479 mosquito is Aedes aegypti. A total of 1.112 containers were inspected and 119 larvae positive container. Containers are the most abundant larvae are located in the bathtub in the house.  There was the relation between knowledge about dengue vector and PSN with larva’s existence (p=0,0001). There was the relation between PSN practice with larva’s existence (p=0,0001). The suggestion for all to do PSN practice regularly with assistance so that the existence of larvae in Ngaliyan district progress can be monitored.